Learning from Cuban avidity - Abd Razak, Dzulkifli (2003)
MALAYSIA, like Cuba, views science and technology (S&T) as important in advancing its socioeconomic status. S&T are high priorities in Malaysia's quest to be a developed country as envisaged under the framework of Vision 2020. In fact, one of the challenges of Vision 2020 is to build a society that is scientifically progressive, a society that is innovative and forwardlooking; one that is not only a consumer of technology but also a contributor to the scientific and technological community. Much has been achieved in promoting S&T, particularly in transforming Malaysia into an industrial nation. The development of electronic, automotive and more recently, IT industries are some of the S&Tbased ventures that Malaysia can be proud of.